The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.3762/bjoc.9.194
|View full text |Cite
|
Sign up to set email alerts
|

Gallium-containing polymer brush film as efficient supported Lewis acid catalyst in a glass microreactor

Abstract: SummaryPolystyrene sulfonate polymer brushes, grown on the interior of the microchannels in a microreactor, have been used for the anchoring of gallium as a Lewis acid catalyst. Initially, gallium-containing polymer brushes were grown on a flat silicon oxide surface and were characterized by FTIR, ellipsometry, and X-ray photoelectron spectroscopy (XPS). XPS revealed the presence of one gallium per 2–3 styrene sulfonate groups of the polymer brushes. The catalytic activity of the Lewis acid-functionalized brus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…They successfully used Ga(III) triflate as the catalyst in acetonitrile as solvent at 90 °C, 5 atm pressure, monitoring the conversions by online UV-Vis spectroscopy by following the extinction of the substrate at a specific wavelength. Sardarian and co-workers explored, under milder condition, conversion of the oxime 2 into the nitrile 36 in the presence of diethyl chlorophosphate, getting excellent yields (94%) and shorter reaction time [51].…”
Section: Conversion Of 9-anthraldehyde Oxime To Nitrilementioning
confidence: 99%
“…They successfully used Ga(III) triflate as the catalyst in acetonitrile as solvent at 90 °C, 5 atm pressure, monitoring the conversions by online UV-Vis spectroscopy by following the extinction of the substrate at a specific wavelength. Sardarian and co-workers explored, under milder condition, conversion of the oxime 2 into the nitrile 36 in the presence of diethyl chlorophosphate, getting excellent yields (94%) and shorter reaction time [51].…”
Section: Conversion Of 9-anthraldehyde Oxime To Nitrilementioning
confidence: 99%
“…Polystyrene sulfonate polymer brushes, covalently attached onto the interior of the microchannels in a microreactor, were utilized for the anchoring of a Lewis acid catalyst, viz. gallium(III) 98. The catalytic device was used to execute the dehydration of oximes and the formation of oxazoles by ring closure of ortho ‐hydroxy oximes.…”
Section: Wall‐coated Microreactorsmentioning
confidence: 99%
“…Recently, Verboom and co‐workers demonstrated that random copolymer brushes that consist of mixed active and cooperative segments significantly improved the performance of the corresponding catalytic homopolymer brushes 9l. Noteworthy, polymer brushes have been employed recently for the immobilization of catalysts on the walls of glass microreactors 9c,i,j,l,m. 10d, 11e Apart from these limited examples, polymer brushes have received little attention for use in catalysis.…”
Section: Introductionmentioning
confidence: 99%